2006
DOI: 10.1029/2006gl026122
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake recurrence as a record breaking process

Abstract: Extending the central concept of recurrence times for a point process to recurrent events in space-time allows us to characterize seismicity as a record breaking process using only spatiotemporal relations among events. Linking record breaking events with edges between nodes in a graph generates a complex dynamical network isolated from any length, time or magnitude scales set by the observer. For Southern California, the network of recurrences reveals new statistical features of seismicity with robust scaling… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 18 publications
(23 reference statements)
7
55
0
Order By: Relevance
“…Davidsen et al (2008) incorporated the spatial information in the criteria for identifying the recurrence of a particular event. When applied to seismicity, they observed scaling laws for both the spatial and temporal separation distances between recurrences (Davidsen et al, 2006). Baiesi and Paczuski (2004) included the magnitude information via the Gutenberg-Richter law in creating a spacetime window for aftershock collection, revealing a scale-free network of correlated earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Davidsen et al (2008) incorporated the spatial information in the criteria for identifying the recurrence of a particular event. When applied to seismicity, they observed scaling laws for both the spatial and temporal separation distances between recurrences (Davidsen et al, 2006). Baiesi and Paczuski (2004) included the magnitude information via the Gutenberg-Richter law in creating a spacetime window for aftershock collection, revealing a scale-free network of correlated earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…The complex network-based analysis provides a new approach for nonlinear time series analysis and offers a complementary view to the traditional recurrence quantification analysis (RQA). It has been demonstrated that complex network measures can be usefully applied to: classify nonlinear dynamics of complex systems [6][7][8]; describe causal signatures in seismic activity [9][10][11]; and interpret the geometric properties of an underlying system [4], among many other applications.…”
Section: Introductionmentioning
confidence: 99%
“…Complex networks are increasingly being used to study geophysical systems (Baiesi and Paczuski, 2004;Davidsen et al, 2006Davidsen et al, , 2008Peixoto and Davidsen, 2008;Peixoto et al, 2010;Gu et al, 2013;Zaliapin and Ben-Zion, 2013;Zanardo et al, 2013;Dodds and Rothman, 2000;Mantilla et al, 2006;Feng and Dijkstra, 2014;Bassett et al, 2012). Climate dynamics in particular have been an object of much attention where dynamical networks (also called functional or interaction networks) have been used to study phenomena such as: long-range correlation in the atmosphere known as teleconnections Kawale et al, 2011); climate models (Donges et al, 2009a, b); El Niño Southern Oscillation (Yamasaki et al, 2008;Martin et al, 2013); with more analyses continuously being carried out (Steinhaeuser et al, 2012;Ebert-Uphoff and Deng, 2012;Deza et al, 2013).…”
Section: Introductionmentioning
confidence: 99%